2014
DOI: 10.1002/cm.21190
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical effects of EB1 on microtubules depend on GTP hydrolysis state and presence of paclitaxel

Abstract: Using the nonhydrolyzable GTP analog GMPCPP and the slowly hydrolyzable GTPγS, we polymerize microtubules that recapitulate the end binding behavior of the plus end interacting protein (+TIP) EB1 along their entire length, and use these to investigate the impact of EB1 binding on microtubule mechanics. To measure the stiffness of single filaments, we use a spectral analysis method to determine the ensemble of shapes adopted by a freely diffusing, fluorescently labeled microtubule. We find that the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 62 publications
5
30
2
Order By: Relevance
“…One study tested addition of paclitaxel to GMPCPP-MTs after polymerization and found no change in stiffness [114]. Another study confirmed this result while also finding that when paclitaxel is present during polymerization of GMPCPP-microtubules, the stiffness is significantly reduced to nearly half that of the no paclitaxel case, showing that even order of addition (during or after polymerization) is an important factor affecting microtubule flexural rigidity [115]. GTPγS-polymerized microtubules are less stable than GMPCPP-microtubules so paclitaxel is generally included for stabilization.…”
Section: The Effects Of Small Molecule Inhibitors Of Tubulin Depolymementioning
confidence: 58%
See 4 more Smart Citations
“…One study tested addition of paclitaxel to GMPCPP-MTs after polymerization and found no change in stiffness [114]. Another study confirmed this result while also finding that when paclitaxel is present during polymerization of GMPCPP-microtubules, the stiffness is significantly reduced to nearly half that of the no paclitaxel case, showing that even order of addition (during or after polymerization) is an important factor affecting microtubule flexural rigidity [115]. GTPγS-polymerized microtubules are less stable than GMPCPP-microtubules so paclitaxel is generally included for stabilization.…”
Section: The Effects Of Small Molecule Inhibitors Of Tubulin Depolymementioning
confidence: 58%
“…It is clear that microtubule stiffness is sensitive to a large number of parameters: tubulin source [112], polymerization rate [113], presence of GTP or GTP analog [114,115], small molecule stabilizers [115][116][117][118][119][120], and microtubule associating proteins (MAPs) [96,114,115,[121][122][123][124]. While there appear to be consistent stiffness values reported within a particular research group for a fixed condition, the values vary significantly among different laboratories, even under seemingly similar MT preparation conditions.…”
Section: The Challenges Of Measuring Mt Stiffnessmentioning
confidence: 90%
See 3 more Smart Citations